Effects of varying levels of succinylation and hydroxypropylation on functional, thermal and textural characteristics of white sorghum starch. Issue 3 (9th February 2021) - Mehboob, Sundus; Mohsin Ali, Tahira; Shaikh, Marium; Hasnain, Abid
Abstract: Background and objectives: Starch is a versatile storage biopolymer with exceptional physicochemical properties. However, sometimes it owes certain functional inabilities in the native form which could be effectively overcome by chemical modifications to meet specific requirements. The present study was conducted to improve the functional properties of native sorghum starch chemically modifying via succinylation and hydroxypropylation. Native sorghum starch was modified with different concentrations of succinic anhydride and propylene oxide and was subsequently analyzed for physicochemical, thermal, and textural properties. Findings: The swelling power and water retention capacity tend to improve upon substitution with succinyl and hydroxypropyl groups while succinylation did not have any pronounced effect on solubility of sorghum starch. All modified starches resulted in more clear starch paste than native starch but hydroxypropylated starch pastes were the most transparent to light. Succinylation did not bring about any change in pasting temperature; however, peak viscosity, hot paste viscosity, and cold paste viscosity increased significantly. Hydroxypropylated starches exhibited lower pasting temperature, higher peak viscosity for only starch substituted with 30% propylene oxide. Thermal gelatinization temperatures and enthalpy of gelatinization were significantly reduced after hydroxypropylation of sorghum starch. Percent retrogradation (%R) was significantly reduced for starches treated with 3% and 4% succinic anhydride and for all hydroxypropylated starches. Conclusions: We concluded that hydroxypropylated starch substituted with 30% reagent exhibited the most desirable physicochemical properties and the lowest retrogradation. Significance and novelty: This study highlighted the benefits of using different concentrations of succinic anhydride and propylene oxide to improve the functional properties of sorghum starch.